The Future Evolution of the Mortality Acceleration Due to the COVID-19: The Charlson Comorbidity Index in Stochastic Setting - Carannante, Maria; D'Amato, Valeria; Iaccarino, Guido (Frontiers in Cardiovascular Medicine, 2022)
The empirical evidence from different countries point out many of those who die from coronavirus would have died anyway in the relatively near future due to their existing frailties or co-morbidities. The acceleration of the mortality conceives the underlying insight according to deaths are ‘accelerated’ ahead of schedule due to Covid-19. Starting from this idea, we forecast the future mortality acceleration, based on the relative frailty deterioration due to the presence of the comorbidities at Covid-19 diagnosis. Accordingly, we explicitly determine the contribution of each comorbidity on the acceleration forecasting, showing the future trend of the excess of deaths due to the Covid-19. To this aim, our proposal consists in developing a revised Charlson Comorbidity Index in a stochastic environment. Based on a post-stratification scheme, we obtain an unbiased frailty index that varies by age, centred on the reference population.